1986
DOI: 10.5271/sjweh.2117
|View full text |Cite
|
Sign up to set email alerts
|

Changes in water vapor loss from the skin of metal industry workers monitored during exposure to oils.

Abstract: Changes in water vapor loss from the skin of metal industry workers monitored during exposure to oils. by Coenraads PJ, Lee J, Pinnagoda J This article in PubMed: www.ncbi.nlm.nih.gov/pubmed/2947320 Environ Health 12 (1986) [494][495][496][497][498] Changes in water vapor loss from the skin of metal industry workers monitored during exposure to oils by Pieter-Jan Coenraads MD, MPH, James Lee, MSe, PhD, Jaliya Pinnagoda, SSe 1 COENRAADS P-J, LEE J, PINNAGODA 1. Changes in water vapor loss from the skin of met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…Hence, monitoring of TEWL, only in the occupationally primarily exposed area (dorsum of hand) may become useful in the secondary prevention of occupational dermatitis (8, 20). While the subtle response of the cutaneous barrier as monitored with TEWL measurements is associated with the clinical course of hand dermatitis, baseline (pre‐exposure) TEWL was not a predictor for the development of contact dermatitis, similar to findings reported by other authors (7, 8, 21).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, monitoring of TEWL, only in the occupationally primarily exposed area (dorsum of hand) may become useful in the secondary prevention of occupational dermatitis (8, 20). While the subtle response of the cutaneous barrier as monitored with TEWL measurements is associated with the clinical course of hand dermatitis, baseline (pre‐exposure) TEWL was not a predictor for the development of contact dermatitis, similar to findings reported by other authors (7, 8, 21).…”
Section: Discussionmentioning
confidence: 99%
“…TEWL, SCH and SSpH have been measured on a wide variety of anatomical positions in occupational settings (refer to Figure ). TEWL measurements have been made on the dorsum (back) of hand, volar forearm, extensor forearm, index finger, thumb, palm, wrist, neck and forehead…”
Section: Skin Parameter Measurement—skin Related and Other Aspectsmentioning
confidence: 99%
“…The measurement of water loss in occupational settings dates as far back as 1986, when skin vapour loss (SVL) was measured on the skin of metal industry workers exposed to mineral oil and water‐soluble oil . SVL is a measurement of the water loss from the skin, which includes TEWL, as well as a small quantity of water vapour from the sweat glands.…”
Section: Transepidermal Water Loss In Occupational Settingsmentioning
confidence: 99%
“…Straight oils, mineral oil-based or ethanolamine-based fluids can be correlated with the development of a variety of cancers such as leukemia, laryngeal, rectal, esophageal, stomach and pancreas cancer.7-9 The route for chronic intoxication are mainly stained hands via ingestion and/or adsorption and with regard to early formulations of mineral oils we also see a direct carcinogenicity for the skin.8,10 In addition, Ormerod et al reports sensitization from polyamines in offshore workers handling drilling muds.11 Using the most important parameters for the injury of the epidermal skin barrier function, transepidermal water loss and vapor loss from non-sweating skin, Goh et al as well as Coenraads et al showed the high irritation potency of straight mineral oils and cutting fluids among workers in the metal industry. [12][13] No wonder, that both authors also report about the development of irritant contact dermatitis among their study populations, as the break down of the skin barrier initiates that kind of eczema.3 In the light of the literature, it is quite astonishing that neither publications exist defining the extent of occupational skin diseases within the mineral oil and petrol industry, nor were any standardized measures developed to protect workers from the multiple dangers of irritant hand dermatitis.…”
Section: Introductionmentioning
confidence: 99%